Patterns of femoral neck fracture and its treatment methods in patients with osteogenesis imperfecta. Issue 2 (March 2022) - Hong, Wan Kee; Lee, Doo Jae; Chung, HoeJoeng; Lim, Chaemoon; Shin, Chang Ho; Yoo, Won Joon; Cho, Tae-Joon
Abstract : Femoral neck fracture (FNF) is not common in osteogenesis imperfecta patients but may result in serious complications if not properly treated in due time. We present three types of FNF in osteogenesis imperfecta and their characteristics, treatment methods and outcomes. Cases of FNF followed for more than 2 years were selected from the osteogenesis imperfecta database. Medical records and radiographs were reviewed to obtain demographic information and to determine ambulatory status, mode of injury, location of the fracture line, presence of preexisting implants, treatment methods and complications. Outcomes were evaluated according to the radiographic results and ambulatory function. The study investigated 15 FNFs in 10 patients including 1 Sillence type I, 1 type III and 8 type IV. They were either community or household ambulators. The mean age at fracture was 11.7 years. The fractures were followed for an average of 6.3 years. Six fractures were attributed to accidental injuries and nine without noticeable trauma. The fracture pattern was categorized into undisplaced ( n = 3), angulated-stable ( n = 7) or displaced-unstable ( n = 5) types. Five fractures were fixed in-situ using screws or Kirschner wires. Other five fractures were treated by closed reduction and screw fixation and the remaining five fractures were managed by femoral valgus osteotomy. Bony union was achieved, and prefracture ambulatory status was restored in all cases. A high index of suspicion is required in the diagnosis of undisplaced or angulated-stable fractures. Treatment is usually challenging, but a judicious approach considering the fracture pattern and patient characteristics result in successful outcomes. The angulated-stable pattern of fracture is unique in osteogenesis imperfecta patients and requires special attention.